THE INFLUENCE OF ISRA AWARD ON THE INVESTOR’S DECISIONS - Febrianto, Muhammad Rizky; Sukoharsono, Eko Ganis (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to find the evidence whether the implementation of Indonesian Sustainability Reporting Award (ISRA) is able to affect the investor’s decision. This study uses the qualitative research method meanwhile, a content analysis of stock movement data for 5 days before and after the ISRA 2011 is chosen as the research measurement tool. ISRA itself constitutes an award held by the National Center for Sustainability Reporting (NCSR) which aims to motivate and accelerate the sustainability reporting of Indonesian companies by rewarding the outstanding attempts to communicate the corporate performance in three aspects (economics, social, and environment). Meanwhile, this award exists because Corporate Social Responsibility (CSR) activity that is undertaken by every company in Indonesia is required by the Government of Indonesia through the Law 25 of 2007 on Capital Investments and the Law 40 of 2007 on Limited Companies. It was found in this study that there was the difference in investor’s decision. Such decision was expressed in three different forms of reactions, namely positive reaction, no reaction, and negative reaction.   Keywords: Indonesian Sustainability Reporting Award (ISRA) 2011, Investor’s Decision, Content Analysis, Corporate Social Responsibility (CSR), Positive Reaction, No Reaction, and Negative Reaction.